Flumazenil; a Medication Considered for Reversal of Benzodiazepine Overdose in Rapid Tranquillisation, but Could Administering It Be Hazardous for Both Patient and Doctor? A Rapid Review Required - Rebecca Hutchinson (BJPsych Open)
Aims: Flumazenil is a benzodiazepine antagonist and competitively inhibits binding at the benzodiazepine receptor. In Northern Ireland (NI) mental health hospitals, and across other UK mental health hospitals, flumazenil is documented as the reversal agent for use in iatrogenic benzodiazepine overdose (usually lorazepam), as part of the rapid tranquillisation protocol. The indications for its use, contraindications and risks of use need to be considered carefully for safe and appropriate prescribing.